Target Product Profile for a point-of-care diagnostic test for dermal leishmaniases. (May 2019) - Cruz, Israel; Albertini, Audrey; Barbeitas, Mady; Arana, Byron; Picado, Albert; Ruiz-Postigo, Jose A.; Ndung'u, Joseph M.
Abstract: Objectives: Localized cutaneous leishmaniasis and its evolving forms diffuse cutaneous leishmaniasis, mucosal leishmaniasis and cutaneous leishmaniasis recidivans, together with the visceral leishmaniasis sequelae post-kala azar dermal leishmaniasis account for about one million dermal leishmaniases cases per year worldwide. Although not lethal, the dermal leishmaniases cause chronic and disfiguring skin lesions, which are an important cause of morbidity and stigma. Microscopy remains the reference test for diagnosis of dermal leishmaniasis; however, it has low and variable sensitivity and requires well trained personnel. The technical complexity and cost of the more sensitive molecular techniques (e.g. PCR) limits their application in routine diagnosis in endemic areas. Point-of-care (POC) tests for early diagnosis are much needed in order to benefit both patients and communities, by reducing the risk of both sequelae and Leishmania transmission. To this end we developed a Target Product Profile (TPP) for a POC test for dermal leishmaniases. Methods: The TPP was defined through several rounds of discussions and by consensus with stakeholders and experts in dermal leishmaniases from different type of organizations and endemic regions. Results and conclusions: A rapid, simple and robust test that can be implemented in resource-limited settings, enabling decentralized diagnosis and treatment of dermal leishmaniasis should be developed. Ideally it should enable the diagnosis of all forms of dermal leishmaniasis, but the minimally accepted target would be localized cutaneous leishmaniasis. A minimum sensitivity of 95% and specificity of 90% would be required. The consensus was that the POC test should target Leishmania antigens.